The Relationship of Motor Ability with Basic Technical Skills for Playing Football - Muhammad Aditya Rajak Samudra; Nurhidayat, Nurhidayat; Pungki Indarto (Fair Play, 2024)
This research aims to determine the relationship between motor ability and basic technical skills for playing football in football UKM students at Muhammadiyah University, Surakarta. The type of research used is quantitative research with a correlational research design. This research was carried out on the psychology football field, Campus 2, Muhammadiyah University, Surakarta, Sukoharjo Regency, Central Java. The population in this study were all students who were members of the Muhammadiyah University of Surakarta football UKM, totaling 80 students with a sample of 20 students. The test instruments used are motor ability tests and basic football technical skills tests.This research data analysis usesnormality test, linearity test and correlation test. From several tests carried out, the results showed that there was a significant relationship between motor ability and basic technical skills for playing football in football UKM students at Muhammadiyah University, Surakarta.